Cerebrospinal fluid acid-base status and lactate and pyruvate concentrations after convulsions of varied duration and aetiology in children. Issue 11 (November 1977) - Simpson, H; Habel, A H; George, E L
Abstract : Twenty-two infants and children were studied after convulsions of varied cause and duration. Arterial and CSF acid-base variables, lactate and pyruvate concentrations, and lactate/pyruvate ratios were measured between 3 and 18 hours after convulsive episodes. Biochemical signs of cerebral hypoxia were found in 7 patients with prolonged (greater than 30 minutes) or recurrent short convulsions. These signs were absent in patients with single short convulsions. These findings indicate that cerebral hypoxia and possible brain damage is a hazard of prolonged or rapidly recurring short convulsions.